Adsorption and biodegradation removal of methylene blue in a down-flow hanging filter reactor incorporating natural adsorbent. Issue 3 (28th January 2021) - Nguyet, Phan Nhu; Watari, Takahiro; Hirakata, Yuga; Hatamoto, Masashi; Yamaguchi, Takashi
ABSTRACT: This study was carried out to explore the importance of adsorption and biodegradation mechanisms for methylene blue (MB) removal by a novel natural adsorbent (purified coconut fibre; PCF) incorporated to a down-flow hanging fibre (DHF) reactor. An adsorption DHF (Ads-DHF) reactor demonstrated the adsorption removal mechanism, while a combined adsorption-biological DHF (Bio-DHF) reactor simulated the processes of both adsorption and biodegradation were investigated for the MB removal capability. PCF prepared from coconut fibre waste was applied as a media in the DHF reactors. The process performance and the removal mechanisms of the DHF reactors were evaluated for 62 days. The results showed that a total MB removal efficiency of 93 ± 7% was achieved for the Bio-DHF reactor and 36 ± 25% for the Ads-DHF reactor. The combined adsorption and biological degradation in the Bio-DHF reactor enhanced the removal efficiency and the life-time of the reactor compared with the performance of the adsorption process alone in the Ads-DHF reactor. Moreover, microbial community analysis revealed that microorganisms, commonly involved in the biodegradation of dyes, were predominant in the Bio-DHF reactor. The PCF media of the Bio-DHF reactor was essential to keep the dye degrading bacteria in the reactor. Therefore, it can be concluded that the Bio-DHF reactor is an appropriate treatment system for treating dyes wastewater. This research is significant and useful for environmental protection and reuse of biomass wastes. GRAPHICAL ABSTRACT: UF0001